EMPOWERMENT OF EARTHWORMS BREEDER IN DESA KEJI UNGARAN BARAT - Petrus - Maharsi (Admisi dan Bisnis, 2017)
ABSTRACTThe purpose of the cultivation of earthworms development program  in Keji village West Ungaran is to improve the product quantity and quality  produced by the farmers. The target of this program is a group of earthworm breeder named Margo Mulyo. Over the past three years, the quantity and also the quality of the product is still not match with the demand that is very big. The production capacity  is only arround 30 kg per month wheter the demand is more than 100 kg up to 1.000 kg per month. The main problem is there is the breeder has no appropriate facilities such as special place for breeding the earthworms.  Besides, the packaging is also very simple, which just wrapped in plain plastic. So the result is a  low production capacity and also low quality of the product.  Through the provision of training and an appropriate building for breeding earthworms as a standard specification, the business group is expected to produce earthworms in a better quality and higher quantity and can fullfil the customers demand. The method is to achieve this goal is to construct an appropriate building for breeding earthworms and  technical training in  effective marketing management. The development of  the earthworms building is needs to be done, because there is no adequate house of theearthwors. With the adoption of better production equipment and have certain standards and making adequate packaging, the group hopes can  be able to improve the quantity and quality of the products and ultimately increase sales volume and revenue. Keywords: Development, Cultivation, Earthworms, Capacity, Quality ABSTRAKTujuan dari program pengembangan budidaya cacing tanah di desa Keji Barat Ungaran adalah untuk meningkatkan kuantitas dan kualitas produk yang dihasilkan oleh petani. Sasaran program ini adalah kelompok peternak cacing tanah bernama Margo Mulyo. Selama tiga tahun terakhir, kuantitas dan juga kualitas produk masih belum sesuai dengan permintaan yang sangat besar. Kapasitas produksi hanya diseluruh 30 kg per bulan sedangkan permintaan lebih dari 100 kg hingga 1.000 kg per bulan. Masalah utama adalah belum  ada fasilitas yang sesuai seperti tempat yang khusus untuk pembibitan cacing tanah. Selain itu, kemasan juga sangat sederhana, yang hanya dibungkus plastik polos. Jadi hasilnya adalah kapasitas produksi rendah dan kualitas juga rendah. Melalui penyediaan pelatihan dan bangunan yang tepat untuk beternak cacing tanah sesuai dengan spesifikasi standar, kelompok peternak cacing tanah diharapkan bisa menghasilkan cacing tanah dalam kualitas yang lebih baik dan kuantitas yang lebih tinggi dan dapat memenuhi permintaan pelanggan. Metode untuk mencapai tujuan ini adalah dengan membangun sebuah bangunan yang tepat untuk berkembang biak cacing tanah dan pelatihan teknis dalam manajemen pemasaran yang efektif. Pembuatan bangunan cacing tanah perlu dilakukan, karena belum ada bangunan yang memadai untuk beternak cacing tanah. Dengan menggunakan peralatan produksi yang lebih baik dan memiliki standar tertentu dan kemasan yang memadai, diharapkan kelompok ini dapat meningkatkan kuantitas dan kualitas produk dan pada akhirnya meningkatkan volume penjualan dan pendapatannya. Kata kunci: Pengembangan; Beternak; Cacing tanah; Kuantitas; Kualita